1998
DOI: 10.2807/esm.03.02.00102-en
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of mumps in the Province of León Spain 1995-1996

Abstract: In Spain mumps vaccine is given at the age of 15 months together with measles and rubella vaccines since 1982. Increased numbers of cases and outbreaks of mumps appeared in several autonomous communities in 1995. An outbreak of mumps in the province of.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…In a recent study conducted at a university in Kansas during an outbreak in 2006, case patients were more likely than their roommates without mumps to have been last vaccinated with the second dose у10 years earlier [10]. In addition, studies conducted in the United Kingdom and Europe revealed lower vaccine effectiveness in older cohorts and an increased risk of developing mumps with increased time after vaccination [39,40,48].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study conducted at a university in Kansas during an outbreak in 2006, case patients were more likely than their roommates without mumps to have been last vaccinated with the second dose у10 years earlier [10]. In addition, studies conducted in the United Kingdom and Europe revealed lower vaccine effectiveness in older cohorts and an increased risk of developing mumps with increased time after vaccination [39,40,48].…”
Section: Resultsmentioning
confidence: 99%
“…Mumps continues to be endemic in various regions of the world, and the number of outbreaks has recently increased (9,10). Controlling and eliminating rubella is important in public health because of the teratogenic effects that may occur when the infection is acquired during the first months of gestation.…”
mentioning
confidence: 99%
“…Alle EPIET-Trai nees wa ren an ei ner oder meh re ren na tio na len oder in ter natio na len Aus bruchs un ter su chun gen betei ligt, bei spiels wei se zu MRSA, E. coli, Le gio nel len, Q-Fie ber, Mumps, He pati tis A, Ty phus und Ro ta vi ren [13,14,15,16,17,18,19,20,21,22]. EPIET-Trai nees führ ten eben falls ver schie de ne Sur veil lance pro jek te zu Le gio nel len, se xu ell über-trag ba ren In fek tio nen oder Cam py lo b acter durch [4, 23,24,25,26].…”
Section: Trai Nings Zie Leunclassified